2011
DOI: 10.1038/nm.2285
|View full text |Cite
|
Sign up to set email alerts
|

A multistage tuberculosis vaccine that confers efficient protection before and after exposure

Abstract: All tuberculosis vaccines currently in clinical trials are designed as prophylactic vaccines based on early expressed antigens. We have developed a multistage vaccination strategy in which the early antigens Ag85B and 6-kDa early secretory antigenic target (ESAT-6) are combined with the latency-associated protein Rv2660c (H56 vaccine). In CB6F1 mice we show that Rv2660c is stably expressed in late stages of infection despite an overall reduced transcription. The H56 vaccine promotes a T cell response against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
452
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 479 publications
(490 citation statements)
references
References 37 publications
27
452
1
6
Order By: Relevance
“…In mouse models, H56 elicited a strong multifunctional CD4 + T-cells response and limited reactivation of latent TB [63]. …”
Section: Resultsmentioning
confidence: 99%
“…In mouse models, H56 elicited a strong multifunctional CD4 + T-cells response and limited reactivation of latent TB [63]. …”
Section: Resultsmentioning
confidence: 99%
“…Vaccination with multiple immunodominant antigens from Mtb may be important to drive broad repertoire coverage to improve the protective effect of any new vaccination. 8,9 The most prominent antigens described for induction of cellmediated immunity have been members of the esx family. [10][11][12][13] The esx family consists of 23 members that are approximately 100 amino acids in length, with 13 members that can be further divided into 3 distinct subfamilies based on high sequence homology between the members.…”
Section: Introductionmentioning
confidence: 99%
“…Rv2660c, a latency-associated protein, has recently been identified as an effective post-exposure vaccine. 31 Nevertheless, the high abundance of antigen is not always correlated with the level protective efficacy. For example, while the expression of ESAT-6 is ten times higher than that of Ag85 complexes in the lungs of mouse, studies have shown that the bacterial burdens in the lungs are similarly reduced between mice immunized with ESAT-6 and Ag85B.…”
Section: Discussionmentioning
confidence: 99%